Real-world evidence of remdesivir in formerly hospitalized COVID-19 patients: patient-reported and functional outcomes - Dorottya Fésü; Enikő Bárczi; Balázs Csoma; Lőrinc Polivka; Márton Boga; Gábor Horváth; János Tamás Varga; Szilvia Sebők; Veronika Müller (BMC Infectious Diseases)
Abstract Background Post-COVID condition (PCC) is characterized by persisting symptoms after the resolution of acute COVID-19. Remdesivir (RDV), a broad-spectrum antiviral drug, has been widely used in patients hospitalized with COVID-19 requiring oxygen therapy. We aimed to evaluate the effects of RDV on PCC by assessing patient-reported and functional outcomes. Methods We used the data from a single-center registry, including formerly hospitalized post-COVID patients (N = 293). Propensity score matching (PSM) was used (16 criteria, 1:1 ratio) to obtain two comparable groups: those who received standard-of-care (SOC, N = 94) and those treated with RDV in addition to SOC (SOC + RDV, N = 94). Primary outcomes were asymptomatic status and at least 50% symptom score reduction at post-COVID follow-up. Secondary outcomes included results of pulmonary function (PF) tests, 6-minute walk test (6MWT), and quality-of-life (QoL) questionnaires. Results After PSM, baseline patient characteristics showed no significant differences between the two groups. Most patients were still symptomatic (60% vs. 66%). In the SOC + RDV group, the use of oxygen supplementation (94 vs. 80%, p = 0.005) and steroids (97 vs. 88%, p = 0.027) during infection were higher, while patients presented at their post-COVID visits earlier (median 68 vs. 97 days, p = 0.003). Complete or at least 50% symptom resolution were reported at a significantly earlier stage after infection in the SOC + RDV group compared to the SOC group (multivariable-adjusted HR = 2.28, 95% CI = 1.33–3.92, p = 0.003; and HR = 2.08, 95% CI = 1.43–3.02, p < 0.001; respectively). In the SOC + RDV group, fewer patients experienced sleep disturbances at PCC, and sleep-related questionnaires (Pittsburg Sleep Quality Index, PSQI) results showed significantly better sleep quality (14 vs. 27% and 5.9 vs. 7.7 points, respectively). There were no notable differences in results of PF tests, 6MWT, and other QoL questionnaires. Conclusion In this propensity score matched cohort, the use of RDV was associated with earlier patient reported symptom resolution during the PCC period, while there were no notable differences in functional outcomes. Our results indicate a possible beneficial effect of RDV in terms of faster symptom resolution after COVID19 infection. Graphical abstract